Ovarian Cancer A Clinical and Translational Update - Díaz-Padilla, Iván (IntechOpen, 2013)
"Ovarian Cancer: A Clinical and Translational Update" embraces the most recent advances in diagnosis and treatment of ovarian cancer. With the valuable collaboration of international experts in the field, this book is intended to provide the readership with a comprehensive update in the subject of epithelial ovarian cancer.